A Prospective Study of Depression Following Combat Deployment in Support of the Wars in Iraq and Afghanistan - Wells, Timothy S. (American Public Health Association, 2010)
Objective. We investigated relations between deployment and new-onset depression among US service members recently deployed to the wars in Iraq and Afghanistan. Methods. We included 40 219 Millennium Cohort Study participants who completed baseline and follow-up questionnaires and met inclusion criteria. Participants were identified with depression if they met the Primary Care Evaluation of Mental Disorders Patient Health Questionnaire criteria for depression at follow-up, but not at baseline. Results. Deployed men and women with combat exposures had the highest onset of depression, followed by those not deployed and those deployed without combat exposures. Combat-deployed men and women were at increased risk for new-onset depression compared with nondeployed men and women (men: adjusted odds ratio [AOR] = 1.32; 95% confidence interval [CI] = 1.13, 1.54; women: AOR = 2.13; 95% CI = 1.70, 2.65). Conversely, deployment without combat exposures led to decreased risk for new-onset depression compared with those who did not deploy (men: AOR = 0.66; 95% CI = 0.53, 0.83; women: AOR = 0.65; 95% CI = 0.47, 0.89). Conclusions. Deployment with combat exposures is a risk factor for new-onset depression among US service members. Post-deployment screening may be beneficial for US service members exposed to combat.